Metodología para la tipificación hidromorfológica de los cursos fluviales de Aragón en aplicaciones de la directiva marco de aguas (2000/60/CE) - Ollero Ojeda, Alfredo; Echeverría Arnedo, María Teresa; Sánchez Fabre, Miguel; Auría Izquierdo, Virginia; Ballarín Ferrer, Daniel; Mora Mur, Daniel (Geographicalia, 2016)
Classification of the different types of rivers and streams is a key process in the application of the Directive 2000/60/EC to determine the ecological quality of rivers. We report a simple method of characterization based on hydromorphological standards and on the description criteria proposed by the Directive. Three overall groups of characterization criteria are established: topographical, hydroclimatic and geomorphological. After that a simplification process is performed, leading to the definition of 13 basic types applicable to the Aragonese drainage network.